Transient Neonatal Diabetes Mellitus with the Rare Association of Nonsuppurative Sialadenitis and Genetic Defects in 6q24 - Manal Mustafa; Nitin Ramdas; Mahmoud Elhalik; Arif Faquih (Case Reports in Pediatrics)
Background. Transient neonatal diabetes mellitus (TNDM) is the most common cause of diabetes in the first week of life, with an overall incidence of 1 in 90,000 to 160,000 live births. TNDM occurs soon after birth and undergoes spontaneous remission during infancy; however, it may relapse to a permanent form of diabetes mellitus in childhood or adolescence. We report a case of TNDM due to hypomethylation on chromosome 6q24, associated with a rare clinical finding of nonsuppurative submandibular sialadenitis managed by subcutaneous insulin, and who underwent remission by three months of age. Case Presentation. We report a male neonate of Arab ancestry delivered by caesarean section at 37 weeks of gestation. He had intrauterine growth retardation with a birth weight of 2.099 kg. He presented with hyperglycemia on the first day of life, which was managed with parenteral insulin infusion. Blood glucose control was initially difficult to achieve due to difficulties in preparing such small doses of insulin and the significant variations in blood glucose concentrations, without ketosis. Blood tests revealed low serum insulin and C-peptide levels. Genetic analysis revealed multiple loci hypomethylation of the PLAGL1/HYMAI-DMR in the TNDM region in chromosome 6q24 and two pathogenic heterozygous variants in the ZFP57 gene. Segregation analysis showed that both parents were heterozygous carriers of familial ZFP57 variants. The clinical course was associated with bilateral nonsuppurative sialadenitis, which is extremely rare among newborns. Conclusion. Sialadenitis is a well-known phenomenon that is rarely diagnosed in neonates. To the best of our knowledge, this is the first case report to describe the exceedingly rare association of nonsuppurative submandibular sialadenitis in a neonate with TNDM due to multiple loci hypomethylation of the PLAGL1/HYMAI-DMR in the TNDM region in 6q24 and heterozygous pathogenic variants in the ZFP57 gene.